Reactions of diphenic acid with carbamide as a way to acyclic and cyclic amides of diphenic acid; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Yanovskiy V. А.; Baturin D. М.; Yagovkin А. Yu.; Bakibayev А. А. (Chemistry, 2007)
Заглавие с титульного листа